The Feasibility of Constructing Rainwater Harvesting Dams and Their Storage Capacity in Al-Abyadh Valley West of Iraq (Journal of Engineering, 2025)
This study's primary emphasis was locating appropriate locations in the valley of Al-Abyadh for water harvesting dams. Water harvesting techniques are one possible answer for Iraq's water difficulties caused by climate change and the existing dams in the high reaches of rivers, which have exposed the world to severe drought. Water harvesting is collecting water from a specific area, beginning with rainwater in the ground and conserving it by building dams to store it. Valley Al-Abyadh, which extends 268 km and has an area of 4188.96 km2, is situated in Anbar Governorate's western desert. Water flows into the Al-Abyadh valley through four basins. This study aims to examine the four basins hydrologically and analyze the data using the HEC-HMS software to find the best places to put water harvesting dams and how much water they can hold.  ArcGIS 10.8 and HEC_HMS 4.11 were used for the analysis of the maps. 2008–2022, We used real rainfall data from the meteorological and seismic monitoring division. The simulations determined a storage capacity of 1045.69056 M m3 run using actual rainfall data inside Valley Al-Abyadh. Work on rainwater harvesting dams began in the basins of the valley Al-Abyadh. Every basin has reached its maximum storage capacity, respectively14,11,20,10 (46.27584M m3, 42.81984M m3, 63.19296M m3, 65.00736 M m3). The study shows that water from these dams might be used since Valley Al-Abyadh has the highest storage capacity among water harvesting dams and the lowest loss rate.